Taxonomic studies of the genus Phymaturus (Iguania: Liolaemidae): Redescription of Phymaturus patagonicus Koslowsky 1898, and revalidation and redescription of Phymaturus spurcus Barbour 1921 - Lobo Gaviola, Fernando Jose (2005)
Phymaturus spurcus was described by Barbour in 1921. In 1931, Burt and Burt placed this species in the synonymy of Phymaturus patagonicus based on their comparison of one paratype of P. spurcus with one specimen of P. patagonicus. Additionally, Burt and Burt considered P. patagonicus a subspecies of Phymaturus palluma. Although some subsequent authors accepted the synonymy of P. patagonicus with P. palluma, the synonymy of P. spurcus with P. patagonicus has gone unquestioned. We examined the type series of P. patagonicus and P. spurcus, as well as new material collected from the type localities of both species. Based on 47 morphological characters of squamation, gular and nuchal folds, precloacal pores, and morphometric data, we conclude that P. spurcus is a valid species, distinct from P. patagonicus and all other Phymaturus. We agree with Cei and Castro's study in 1973 that the population located west of Dolavon, Chubut Province, Argentina, is P. patagonicus of Koslowsky' study in 1898 Because in the original description Koslowsky failed to designate an holotype, we designate Museo La Plata S-778 as the lectotype of P. patagonicus and restrict its type locality to 40 km west of Dolavon, Chubut Province, Argentina. We provide a redescription of P. patagonicus Koslowsky and a redescription of P. spurcus based on the type series of Barbour's study in 1921, with additional data on intraspecific variation in both species. Copyright 2005 Society for the Study of Amphibians and Reptiles.